"MOF-cloth" formed via supramolecular assembly of NH2-MIL-101(Cr) crystals on dopamine modified polyimide fiber for high temperature fume paper-based filter. (1st July 2019) - Xie, Fan; Zhang, Nan; Zhuo, Longhai; Qin, Panliang; Chen, Shanshan; Wang, Yafang; Lu, Zhaoqing
Abstract: A facile route to rapidly assemble presynthesized MOF [NH2 -MIL-101(Cr)] crystals onto polyimide (PI) fibers at ambient temperature was proposed in this article. Furthermore, PI@PDA@MOF fibers were used to fabricate the paper-based filters for high temperature dust removing by wet-forming process. Prior to this, dopamine was dip-coated onto the surface of inert PI fibers to active the fiber surface. Herein, MOF crystals were chemically induced using β-cyclodextrin (β-CD) and cetyltrimethylammonium bromide (CTAB) as surfactant assembly agents, which quickly self-assembled on the crystal surface and promoted robust chemical surface attachment onto the activated PI@PDA fibers. BET results manifested that the overall surface area of PI@PDA@MOF fibers exceeded 800 m 2 /g with assistance of "MOF-cloth". Filtration performance experimental results indicated that removal efficiency of composites reached as high as 93.05 ± 1.27% at a lower pressure drop of 57.5 Pa and a higher quality factor of 0.0464 Pa -1 for PM0.3 under the high temperature of 260 °C. Graphical abstract: Image 1